Paradigma Terminologi Islam (Muslim) Dan Iman (Mukmin) Atas Larangan Pernikahanantar-Agama Dalam Hukum Islam - Sadari Sadari (STIU Al-Mujtama Pamekasan, 2020)
Debates in theological terms have been occurred among the historical Civilization of Islami. As well as in terms of Islamic law, which have continually developed. This article examines how terms with theological nuances are integrated or at least interconnected. This article examines how the terms Islam (muslim) and Iman (mukmin) are linked to the law on the prohibition of interfaith marriage. This is very interesting, because there has been an resistance to an exciting laws had been replaced by a new that recently created, then those that already exist are replaced by recently created. By using Muhammad Syahrur's paradigm, the article examines more and deeper in the location key of the different meanings of the terms and develooing idioms that devel which are background to the prohibition of interfaith marriage, such as musyrik, kafir, Ahl al-Kitab, Islam, and iman, so that the formula that will be researched is How to find Muhammad Syahrur's paradigm to the term or term for the prohibition of interfaith marriage, then to find out the effects of that and formulate how the law applies to the prohibition of interfaith marriage in Islamic law. The direction of this study uses normative-historical, which tries to find out what kinds of structures that can build an interfaith marriage discourse. By examining and addressing these methods and components to create power relations in the interfaith marriage discourse. It is hoped will be useful for the creation of a more precise understanding and in the end it may contribute the ideas in a broad horizon of knowledge, especially in Islamic family law. Keywords: Paradigm; Interfaith Marriage; Islamic law